2007
DOI: 10.1007/s10562-007-9286-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of Glycerol to Propanediol Over Ru: Polyoxometalate Bifunctional Catalyst

Abstract: Ruthenium-doped (5 wt%) acidic heteropoly salt Cs 2.5 H 0.5 [PW 12 O 40 ] (CsPW) is an active bifunctional catalyst for the one-pot hydrogenolysis of glycerol to 1,2-propanediol (1,2-PDO) in liquid phase, providing 96% selectivity to 1,2-PDO at 21% glycerol conversion at 150°C and an unprecedented low hydrogen pressure of 5 bar. Rhodium catalyst, 5%Rh/CsPW, although less active, shows considerable selectivity to 1,3-PDO (7.1%), with 1,2-PDO being the main product (65%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 23 publications
2
103
0
11
Order By: Relevance
“…Pd-plate-like iron oxide catalysts show higher activity than Pd-rod-like samples with the glycerol conversion/1,2-PDO production increasing with the reduction temperature (200-300 °C) [232,233]. The higher activity shown by the Pd-plate-like iron oxide catalyst was correlated to a higher amount of active sites at the interface [234,235]. Moreover, CO2-TPD measurements reveal an exact correlation between the catalytic activity and the number of basic sites Mauriello et al studied the performance of the 5% Pd/Fe 3 O 4 co-precipitated catalyst in the hydrogenolysis of EG [129].…”
Section: C-c and C-o Bond Breaking In C2-c6 Polyolsmentioning
confidence: 99%
“…Pd-plate-like iron oxide catalysts show higher activity than Pd-rod-like samples with the glycerol conversion/1,2-PDO production increasing with the reduction temperature (200-300 °C) [232,233]. The higher activity shown by the Pd-plate-like iron oxide catalyst was correlated to a higher amount of active sites at the interface [234,235]. Moreover, CO2-TPD measurements reveal an exact correlation between the catalytic activity and the number of basic sites Mauriello et al studied the performance of the 5% Pd/Fe 3 O 4 co-precipitated catalyst in the hydrogenolysis of EG [129].…”
Section: C-c and C-o Bond Breaking In C2-c6 Polyolsmentioning
confidence: 99%
“…The use of noble metal catalysts containing Ru [10,11], Pt [12][13][14], Rh [15][16][17][18], Pd [15,16,19], and Ir [20] have been reported in the hydrogenolysis of glycerol. Metallic systems based on noble metals can be a drawback to development of the hydrogenolysis process.…”
Section: Introductionmentioning
confidence: 99%
“…19 From these reports it can be inferred that acidity promoters and acid co-catalysts enhance the global reaction rate. 26,27 Balaraju and coworkers report that there exists a linear relation between the total acidity of the solid acid catalysts and the glycerol conversion. The same authors found that at 180 °C and 60 atm hydrogen pressure the addition of niobia to a Ru/C base catalyst of moderate acidity increases the total acidity and the resulting activity.…”
Section: Catalytic Activitymentioning
confidence: 99%